Understanding Arab Consumers' Anti-Americanism:: Antecedents and Consequences - Ganideh, Saeb; Elahee, Mohammad (Journal of Comparative International Management)

(untitled) (Management Futures, 2012)
International business researchers have focused primarily on exploring the consumer animosity that has stemmed from the Second World War. This study empirically examines segments of consumers within the Jordanian society who harbour heightened feelings of animosity towards the U.S. and its products. Data were collected from 272 Jordanian consumers, through a structured questionnaire. The results show that older, more educated and more dogmatic Jordanian consumers hold greater anti-American feelings. The results show that the majority of Jordanian consumers are dogmatic and their feelings of animosity towards the U.S. have translated to an unwillingness to purchase U.S products.